Ginástica laboral - um instrumento de melhoria ergonômica e do bem-estar da saúde dos colaboradores do Polo Industrial de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
Several factors such as: illness, lack of attendance, osteomioarticular diseases and their relations with work have been the focus of several studies, since they represent a reality that generates high costs mainly for the companies. In this study, the effects of a physical activity program as an instrument for improving physical well-being in the eyes of the workers of the Industrial Pole of Manaus (PIM) were evidenced. For this, a descriptive qualitative research was carried out by means of a semistructured electronic questionnaire of explanatory character, in which a macroanalysis of the reality related to the self-perception of the physical state of the workers of the Industrial Pole of Manaus was sought. The convenience sample was composed of 140 PIM workers who were willing to answer the electronic questionnaire with closed questions. The results indicated a high level of myoarticular discomfort among the employees surveyed, with attention to some areas that show signs of discomfort due to daily work: the back region presents 44.20% discomfort, legs and feet with 38.5% %, Lumbar 41.3% and shoulders 48.23%. Regarding job satisfaction, workers who practice work gymnastics have a positive perception regarding the improvement of quality of life at work. Concerning the willingness to work, the research demonstrated that workforce participation contributes 77% to increase employee satisfaction, improving the 69.9% working life, as well as its performance within the organization, resulting in In 62% of productivity improvement. The conclusion of this study points to the search for better alternatives to keep the work environment healthier and more productive. Therefore, physical activity is an important tool for improving the well-being of workers in PIM companies. It is important to emphasize that the present dissertation will not revert all the problematic of the work environment, however it can help the health professionals in the formulation of measures that help in the improvement of the quality of life inside and outside the work environment.
Keywords: Atividade física; Qualidade de vida no Trabalho; Ergonomia; Ginástica Laboral; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO